Seed size, number and strategies in annual plants: a comparative functional analysis and synthesis. (19th August 2020) - Hodgson, John G; Montserrat Marti, Gabriel; Šerá, Bozena; Jones, Glynis; Bogaard, Amy; Charles, Mike; Font, Xavier; Ater, Mohammed; Taleb, Abdelkader; Santini, Bianca A; Hmimsa, Younes; Palmer, Carol; et al.
Abstract: Background and Aims: Plants depend fundamentally on establishment from seed. However, protocols in trait-based ecology currently estimate seed size but not seed number. This can be rectified. For annuals, seed number should simply be a positive function of vegetative biomass and a negative function of seed size. Methods: Using published values of comparative seed number as the 'gold standard' and a large functional database, comparative seed yield and number per plant and per m 2 were predicted by multiple regression. Subsequently, ecological variation in each was explored for English and Spanish habitats, newly calculated C-S-R strategies and changed abundance in the British flora. Key Results: As predicted, comparative seed mass yield per plant was consistently a positive function of plant size and competitive ability, and largely independent of seed size. Regressions estimating comparative seed number included, additionally, seed size as a negative function. Relationships differed numerically between regions, habitats and C-S-R strategies. Moreover, some species differed in life history over their geographical range. Comparative seed yield per m 2 was positively correlated with FAO crop yield, and increasing British annuals produced numerous seeds. Nevertheless, predicted values must be viewed as comparative rather than absolute: they varied according to the 'gold standard' predictor used. Moreover, regressions estimating comparative seed yield per m 2 achieved low precision. Conclusions: For the first time, estimates of comparative seed yield and number for >800 annuals and their predictor equations have been produced and the ecological importance of these regenerative traits has been illustrated. 'Regenerative trait-based ecology' remains in its infancy, with work needed on determinate vs. indeterminate flowering ('bet-hedging'), C-S-R methodologies, phylogeny, comparative seed yield per m 2 and changing life history. Nevertheless, this has been a positive start and readers are invited to use estimates for >800 annuals, in the Supplementary data, to help advance 'regenerative trait-based ecology' to the next level.